2018
DOI: 10.3928/19382359-20171218-01
|View full text |Cite
|
Sign up to set email alerts
|

Lead Toxicity in the Pediatric Patient with Sickle Cell Disease: Unique Risks and Management

Abstract: Lead toxicity is the result of lead ingestion, one of the most common ingestions in the pediatric population. Nationwide and statewide efforts to recognize and curtail this epidemic have led to declining rates of toxicity. In patients with sickle cell disease (SCD), lead toxicity can be an elusive diagnosis due to overlapping symptom profiles, and inconsistent follow-up with a primary care physician can make the diagnosis even more difficult. In this article, two illustrative cases of lead toxicity in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Issaivanan et al reported a prevalence of pica to be 76% in younger children [ 6 ]. Jung et al noted multiple additional risk factors for young children to develop lead poisoning including lower socioeconomic status, black race, and Hispanic ethnicity [ 8 ]. In addition, an incomplete blood-brain barrier allows for increased lead penetration to the developing brain [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Issaivanan et al reported a prevalence of pica to be 76% in younger children [ 6 ]. Jung et al noted multiple additional risk factors for young children to develop lead poisoning including lower socioeconomic status, black race, and Hispanic ethnicity [ 8 ]. In addition, an incomplete blood-brain barrier allows for increased lead penetration to the developing brain [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jung et al noted multiple additional risk factors for young children to develop lead poisoning including lower socioeconomic status, black race, and Hispanic ethnicity [ 8 ]. In addition, an incomplete blood-brain barrier allows for increased lead penetration to the developing brain [ 8 ]. Patients with sickle cell anemia more commonly have iron deficiency anemia, which leads to increased gastrointestinal absorption of lead [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation